2020
DOI: 10.1007/s40243-020-00178-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thermal and energy performance of masonry blocks prepared with date palm ash

Abstract: This article evaluates the thermal and energy performance of mortar blocks containing local agricultural waste. The mortar blocks were cast by the replacement of ordinary Portland cement (OPC) with varying amounts of date palm ash (DPA) in the range of 10–30%. Experiments and simulations were carried out to assess the thermal characteristics and energy performance of the specimens. A prototype office building was modeled and simulated in DesignBuilder (Version 6.1.06) with modified blocks prepared with DPA und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Experiments and simulation results depicted that thermal resistance (R-value) of the block loaded with 10%, 20%, and 30% DPA, in comparison to the control block (0% DPA), increased by 9.6%, 8.1%, and 47.4%, respectively. As per Noman Ashraf [36], DPA is a promising insulation material as it can reduce the average monthly indoor temperature by 2 • C without compromising the physical, chemical, and mechanical properties of the block, and cost analysis shows that the block with 30% DPA is the most effective, with a unit cost of $2.76. However, although, in this study, ASTM C90 standard [37] was followed to maintain the density and hence the mechanical strength of the blocks, appropriate analysis to measure the mechanical strength of the blocks was not presented.…”
Section: Aggregate Materialsmentioning
confidence: 97%
“…Experiments and simulation results depicted that thermal resistance (R-value) of the block loaded with 10%, 20%, and 30% DPA, in comparison to the control block (0% DPA), increased by 9.6%, 8.1%, and 47.4%, respectively. As per Noman Ashraf [36], DPA is a promising insulation material as it can reduce the average monthly indoor temperature by 2 • C without compromising the physical, chemical, and mechanical properties of the block, and cost analysis shows that the block with 30% DPA is the most effective, with a unit cost of $2.76. However, although, in this study, ASTM C90 standard [37] was followed to maintain the density and hence the mechanical strength of the blocks, appropriate analysis to measure the mechanical strength of the blocks was not presented.…”
Section: Aggregate Materialsmentioning
confidence: 97%
“…The energy simulations were performed using the EnergyPlus simulation interface in DesignBuilder software (version 7.0.2). According to Ashraf et al [73], EnergyPlus calculations are based on a heat balance technique that takes into account how building models interact with outdoor weather conditions to evaluate the various loads on an hourly basis. The use of EnergyPlus has been recommended by several researchers.…”
Section: Building Energy Performance Simulationmentioning
confidence: 99%
“…The pozzolanic activity in highvolume fly ash mortars after 7 days of cement hydrolysis improved their compressive strength Yousefi et al, [26] It was found that the pit sand-cement mortar prisms after 1, 2, 7 and 28 days achieved optimal strength at 11.11% and about 90% reduction in the permeability Kappel et al, [11] Inclusion of sewage sludge ash modified the performance of mortars to the point that they have compatible compressive strength and workability with those of ordinary mortars Mo et al, [18] It is viable to utilize waste from the paper industry in the form of biomass boiler ash and green liquor dreg to make mortars Blaisi [6] Development of Aluminum (Al) and iron (Fe) mortars using treated fly ash as filler, assimilating 10% in weight of the aggregate and adding it into the mortar dosage as a new formulation. No environmental risk to human health when used as cement replacement [26] The FRM has been proven to be a successful confining technique for concrete beam Orasutthikul et al, [25] Inclusion of straight recycled nylon enhanced the flexural strength of mortars by 41% when compared to that of knotted recycled nylon, recycled PET, and PVA fibers Araya-Leterier et al, [2] There is a positive impact of pig hair as animal fiber to improve the tensile and flexural properties of the mortars Colombo et al, [4] There is a significant influence of FRM to strengthen schist walls…”
Section: Study Focusmentioning
confidence: 99%
“…Araya-Leterier et al, [4] examined the effectiveness of new natural fibers on the damagemechanical performance of mortar. The new natural fibers in the form of pig hair were proven to enhance the tensile and flexural properties of the mortars under the study.…”
Section: Introductionmentioning
confidence: 99%